Changes in the African monsoon region at medium-term time horizon using 12 AR4 coupled models under the A1b emissions scenario. - (:unkn) unknown (My University, 2011)
This study documents simulated precipitation and circulation changes through the 20C3M and A1b scenario. The portray a robust pattern, associating rainfall deficits in subtropical regions with excesses over West Africa, except in Northern Senegal and Mauritania, with a significant enhancement of both the April-June rainy season in 10/12 models and of the July-September rainy season in 8/12 models. Eastward to 5°W a northward shift in latitude of the moisture flux convergence at 850 hPa is evident in 10/11 models (+0.58 ° in mean) and a southward shift in 6 /11 models in the western region (-0.24°) is observed.
Keywords: African Research